2007
DOI: 10.1093/hsw/32.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Spiritually Based Resources in Adaptation to Long-Term Prostate Cancer Survival: Perspectives of Elderly Wives

Abstract: Spiritually based resources (SBR) generally have a salutary effect on coping with cancer diagnosis and treatment. Few studies address this relationship in long-term cancer survivorship, however. As part of a study on long-term prostate cancer survivorship, wives' ways of coping with cancer-related issues were explored through longitudinal interviews.This article describes findings from a subset of women who reported SBR use (N = 28). Wives completing a quality-of-life survey were purposively sampled by age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 0 publications
1
58
0
9
Order By: Relevance
“…Inkeeping with prior research (Morgan et al, 2011;Segrin et al, 2012), patients in this study described their partners as a vital source of support and said that their own well-being and recovery was influenced by how their partner responded. Some participants echoed previous findings that the cancer experience ultimately strengthened their relationship (Dorval et al, 2005;Ka'Opua et al, 2007;Tanner et al, 2011). Dyadic analysis also showed the potential for miscommunication and misunderstandings between patients and partners.…”
Section: Discussionsupporting
confidence: 62%
“…Inkeeping with prior research (Morgan et al, 2011;Segrin et al, 2012), patients in this study described their partners as a vital source of support and said that their own well-being and recovery was influenced by how their partner responded. Some participants echoed previous findings that the cancer experience ultimately strengthened their relationship (Dorval et al, 2005;Ka'Opua et al, 2007;Tanner et al, 2011). Dyadic analysis also showed the potential for miscommunication and misunderstandings between patients and partners.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to the individuals affected by illness or disability, spirituality has also been studied among family members who provide support roles. In their study of spirituality among wives of men with prostate cancer, Ka'opua et al [23] observed that spirituality facilitated adaptation in four areas: marriage preservation and couple intimacy, personal growth and continuous learning, health-related attitudes and community connections. Such findings might also apply to family members of individuals with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…37 Spirituality is defined as “the personal quest for understanding answers about life, about meaning, and about relationship to the sacred or transcendent, which may (or may not) lead to or arise from the development of religious rituals and the formation of community.” 8 Throughout African American history, spirituality has played a prominent role in dealing with adversity, such as serious illness, and providing hope and group identity through religious institutions. 9–13 In the health care context, higher scores on measures of spirituality have been associated with better management of chronic illness, higher levels of health promoting activities, and better health-related quality of life (HRQOL).…”
mentioning
confidence: 99%